Local ecological knowledge about pest control offers novel perspectives for Aye-aye conservation - Holinirina Beby Rabemananjara; Holinirina Beby Rabemananjara; Christof Bodenburg; Dominik Schüßler; Yazdan Asadi; Joelisoa Ratsirarson; Josia Razafindramanana; Josia Razafindramanana; Hantanirina Rasamimanana; Torsten Richter; Anke Meisert (Frontiers in Conservation Science)
IntroductionLocal ecological knowledge (LEK) offers valuable insights into human-wildlife relationships and bears the potential to improve the conservation of controversial species. The Endangered and elusive Aye-aye (Daubentonia madagascariensis) is commonly associated with superstition and negative perceptions that lead to targeted killings, but has recently been related to agricultural benefits. This study explores how knowledge about ecological interactions in clove agroforestry underlies this benefit perception.MethodsThrough surveys (n = 392) and expert interviews (n = 6) across 21 village communities, we assessed Aye-aye-related LEK among clove farmers in northeastern Madagascar. Survey analysis employed a Random Forest model and expert interviews were analyzed using qualitative content analysis.ResultsClove farming experts emphasized the beneficial effect that an Aye-aye has by suppressing invertebrate pest species on clove trees. About 44% of the survey participants related the Aye-aye to pest control and knowledge of its insectivory was identified as a critical factor influencing this benefit knowledge. Diverse levels of LEK about the Aye-aye were recorded and were influenced by gender, socio-economic activities, and geographic location. DiscussionThe results underscore the importance of ecological knowledge as a condition for benefit perception and demonstrate how assessing LEK can provide insights into the perception of cryptic wildlife species. This study illustrates the necessity for targeted conservation actions, sensitive to socio-ecological contexts. Conservation practitioners should employ benefit-based narratives if available and consider local knowledge transmission channels to address negative perceptions of wildlife."